Mechanical and Durability Properties of Induction-Furnace-Slag-Incorporated Recycled Aggregate Concrete - Syed Ishtiaq Ahmad; Md. Shafiqur Rahman (Advances in Civil Engineering)
Most of the steel mills in Bangladesh use induction furnace which produces large quantities of slags that have very little use except land filling. Therefore, feasibility of using this slag is examined in concrete with recycled aggregate, which is another waste product that is generated due to removal of old structures. Concrete with three target strengths, 17.23, 20.68, and 24.13 MPa, was prepared using recycled concrete acquired from a recently demolished building in Dhaka, Bangladesh. Recycled coarse aggregate was replaced with induction furnace slag by 0%, 25%, 50%, 75%, and 100% for each target strength. Samples prepared from these concretes were tested for workability, compressive strength, splitting tensile strength, modulus of elasticity, and durability properties e.g., porosity, absorption, and rapid chloride penetration. Review of test results suggests that workability of concrete was not adversely affected by incorporation of induction furnace slag. For up to 50% of induction furnace slag replacement, both compressive strength and splitting tensile strength increased in recycled aggregate concrete. Further, for all ratios of induction furnace slag replacement, modulus of elasticity increased compared to 100% recycled aggregate concrete. Porosity and absorption also decreased in concrete where up to 50% of recycled aggregate was replaced by induction furnace slag. Considering these, it is concluded that 50% of recycled aggregate can be replaced by induction furnace slag that will result in superior mechanical and durability properties in recycled aggregate concrete.